SOME TECHNICAL AND ECONOMIC ASPECTS OF THE LOCATION OF WIND FARMS - Gospodarek, Łukasz; Trzmiel, Grzegorz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper presents a summary technical and economic analysis of the placement of planned wind turbines. Particular attention was paid to the spatial location and tedious for the public results of wind turbines work, selected economic aspects and the need for monitoring of wind conditions before choosing a location, but also state and current yields using the SCADA system. Draw attention to problems noted should be a sufficient starting point for effective implementation of the investment.